The evolution of the diploma of public health - Falkiner, Ninian M. (Statistical and Social Inquiry Society of Ireland, 1925)
The paper which I have the privilege of presenting to this Society was read, with the approval of the Right Hon. President and Council, at the State Medicine Section of the Academy of Medicine of Ireland in January of the present year and discussed by some of the leading Sanitarians of Ireland. A short abstract of the paper with a full account of the discussion was published in the medical journals.
Read Friday, 14th March, 1924
Keywords: Public health education; Third level education; 314.15